Fun Learning With Youtube and Origami During the COVID-19 Pandemic: Belajar Menyenangkan Dengan Youtube dan Origami Saat Pandemi COVID-19 - Puspitasari, Febiola; Septiyono, Eka Afdi; Kurdi, Fahruddin (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has turned people into individualistic people. The rules that are created cause the entire community to engage in social distancing. Reducing activities outside the home that cause crowds of people. No exception for workers as well as students and students who are studying. With the recommendation of activities at home, workers and students are forced to do work from home and study from home. Through the KKN Back To Village: Innovation Program to Support School Children During Covid-19, it is hoped that the education system in Indonesia can be improved again. Learning with the Youtube platform media is expected to enable students to experience fun learning without feeling bored. And with origami media, it is hoped that target students can continue to preserve traditional culture by learning brain teasers using origami media, which also has a positive influence on increasing creativity and activity and brain memory of target students. The problems and case studies that the authors take are from the Kebonsari Village, Sumbersari District, Jember Regency, East Java. From this KKN activity, the author can increase the knowledge of target students that the Youtube platform is not only a place to watch cartoons or tutorials and etc., but the Youtube platform can also be a place for learning. The author also explains that the Youtube platform must be used for positive things, such as being a place for learning media during the Covid-19 pandemic. Especially during the current pandemic, if target students don't get material from their school, they can learn via the Youtube platform. It is hoped that the target students will be able to undergo online learning smoothly by understanding the material that has been explained well.